2017
DOI: 10.1093/brain/awx243
|View full text |Cite
|
Sign up to set email alerts
|

Tau pathology and neurodegeneration contribute to cognitive impairment in Alzheimer’s disease

Abstract: Neuropathological and in vivo studies have revealed a tight relationship between tau pathology and cognitive impairment across the Alzheimer's disease spectrum. However, tau pathology is also intimately associated with neurodegeneration and amyloid pathology. The aim of the present study was therefore to assess whether grey matter atrophy and amyloid pathology contribute to the relationship between tau pathology, as measured with 18F-AV-1451-PET imaging, and cognitive deficits in Alzheimer's disease. We includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
427
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 535 publications
(504 citation statements)
references
References 54 publications
37
427
4
Order By: Relevance
“…10,26 Briefly, BACS subjects undergo testing to measure performance on global cognitive (eg, MMSE) and specific cognitive tasks including those related to verbal and visual memory, working memory, processing speed, executive function, language, and attention. 10,26 Briefly, BACS subjects undergo testing to measure performance on global cognitive (eg, MMSE) and specific cognitive tasks including those related to verbal and visual memory, working memory, processing speed, executive function, language, and attention.…”
Section: Cognitive Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…10,26 Briefly, BACS subjects undergo testing to measure performance on global cognitive (eg, MMSE) and specific cognitive tasks including those related to verbal and visual memory, working memory, processing speed, executive function, language, and attention. 10,26 Briefly, BACS subjects undergo testing to measure performance on global cognitive (eg, MMSE) and specific cognitive tasks including those related to verbal and visual memory, working memory, processing speed, executive function, language, and attention.…”
Section: Cognitive Assessmentmentioning
confidence: 99%
“…4 Since the recent advent of tau-PET imaging, several cross-sectional studies have shown that FTP retention in vivo reveals patterns consistent with the known neuropathological topology of NFTs. [5][6][7][8][9][10] Very few studies, however, have examined longitudinal FTP imaging. [5][6][7][8][9][10] Very few studies, however, have examined longitudinal FTP imaging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While amyloid-β may be present decades prior to symptom onset 3 , the presence of neocortical tau is temporally more closely related to current cognitive status and degree of neurodegeneration, as convincingly demonstrated by studies utilizing post-mortem tissue, animal models, cerebrospinal fluid and, more recently, the positron emission tomography (PET) tracer [ 18 F]AV1451 [4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, regional [ 18 F]AV1451 retention co-localizes with sites of brain atrophy or hypometabolism 7,18 and has been associated with impairments in specific cognitive domains [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%